REVITALISASI MANAJEMEN SEKOLAH DALAM MENINGKATKANHUBUNGAN TERHADAP MASYARAKAT - Rumina (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
Education is a shared responsibility between the family, government and community, for that the implementation of education requires good relations and cooperation between the three components. Starting from the existence of cases in the field and efforts to improve the quality of education programs in schools, the principal has a very strategic position. Principals can maximize the use of existing resources at schools to solve problems that arise and try as much as possible to utilize the resources available in the community around the school, therefore the need for management revitalization in improving relations with the community, thus solving problems can be overcome as well as possible. The techniques carried out are group meetings, face-to-face meetings, observation and participation, say in paper, the use of other communication media such as TV and telephone radio, planning, organizing, mobilizing, coordinating and controlling school and community relations activities. and schools that are able to make contact relations with their communities will be able to last a long time, instead can move forward. Even though in the beginning the school did not have many facilities, but its managerial ability to approach benefactors is influential people, people who love education and are accompanied by appealing and rational appeal for power, the school can last a long time.